POSSIBLE ROLE OF SODIUM CROMOGLYCATE, A MAST CELL STABILIZER IN HALTING GENTAMICIN NEPHROTOXICITY IN RATS. - Machhan, Neha; Joshi, Jagdish Chandra; Sharma, Saurabh; Budhiraja, R. D. (Asian Journal of Pharmaceutical Research and Development, 2017)
Gentamicin is commonly used in treating life threatening gram-negative bacterial infections, butmajor limitation is its nephrotoxic effect. Free radical generation and reduction in antioxidantdefense mechanisms are mainly considered to be involved in gentamicin induced nephrotoxicity,but the exact mechanism still remains unclear. Mast cells are infiltrated in the inflamed kidneyand their degranulation releases various inflammatory mediators during various renal diseases.We have investigated the possible involvement of mast cell stabilizer sodium cromoglycate[SCG] in halting gentamicinnephrotoxicity in rats. Administration of gentamicin [GM] 100mg/kg i.p. for 10 days in rats induced nephrotoxicity, characterized by significantly [P<0.05]increased serum creatinine, blood urea nitrogen, urinary protein, renal oxidative stress and mastcell density, decreased creatinine clearance and histopathological alterations. Co-administrationof SCG [24mg/kg/day] attenuated significantly [P<0.05], all these biochemical parameters,reduced mast cell density and prevented the histological alteration such as intracellular edema,glomerulus narrowing and necrosis in epithelial cells of the proximal tubules. It is concluded thatmast cells have a detrimental role in gentamicin-induced nephrotoxicity and SCG stabilizes mastcells, reduces the release of various proinflammatory cytokines and thus, prevents the toxiceffects of GM as seen in both, the biochemical and histopathological parameters.